Economic and Clinical Burden Associated With Intensification of Glaucoma Topical Therapy: A US Claims-based Analysis. Issue 3 (29th March 2021) - Patel, Anik R.; Schwartz, Gail F.; Campbell, Joanna H.; Chen, Chi-Chang; McGuiness, Catherine B.; Multani, Jasjit K.; Shih, Vanessa; Smith, Oluwatosin U.
Abstract : Supplemental Digital Content is available in the text. Abstract : Precis: Incremental addition of intraocular pressure–lowering topical drops is associated with shorter-lasting benefit and higher health-related costs with each additional agent, suggesting a need for new treatment options to improve disease control and reduce treatment burden. Purpose: The purpose of this study was to evaluate treatment intensification as a driver of clinical and economic burden in patients receiving topical glaucoma medications for open-angle glaucoma/ocular hypertension. Methods: This retrospective analysis of administrative claims data (January 2011 to July 2017) from the IQVIA PharMetrics Plus database included diagnosed patients who initiated or intensified treatment with 1 to 4 topical glaucoma medications of a different drug class between January 2012 and July 2015 (index date being the first such event during this period). Patients with prior open-angle glaucoma surgery or an equal or greater number of topical glaucoma medication classes during the preindex period were excluded. Treatment intensification rates and eye-related outpatient costs were assessed over 24 months postindex. Results: Of 48, 402 patients (mean age: 61.4 y), 22, 874 (47.3%), 16, 214 (33.5%), 7137 (14.7%), and 2177 (4.5%) received a first, second, third, or fourth medication class, respectively, as their first observed initial or intensified regimen. Among cohorts receiving 1, 2, 3, or 4 medication classes, 7.8%, 12.2%, 17.2%, and 22.6% of patients and 12.6%, 18.5%, 25.9%, and 33.7% of patients had subsequent treatment augmentation (class addition or glaucoma procedure, laser or surgical) within 12 and 24 months postindex, respectively. Eye-related outpatient costs over 24 months increased with each additional topical glaucoma medication class at index [mean (SD): 1610 (3460), 2418 (4863), 2872 (5110), and 3751 (6608) in the 1, 2, 3, or 4 class cohorts, respectively]. Conclusion: Multiple-drop therapies yielded shorter-lasting benefits with each additional agent and were associated with the increased clinical and economic burden.